85 Nationwide sports injury prevention programs: a scoping review. (20th November 2022) - Ross, Andrew; Donaldson, Alex; Poulos, Roslyn
Abstract : Background: Nationwide primary prevention strategies in sport are becoming more popular worldwide. However, the implementation process of sports injury prevention strategies has been questioned. The aim of this review is to highlight worldwide attempts at implementing nationwide sports injury prevention strategies, discern the impact of these strategies and map the nationwide efforts onto the Translating Research into Injury Prevention Practice (TRIPP) framework. Methods: A scoping review methodology using Levac' five stage method was utilised to: (1) identified the research questions, (2) identified relevant studies, (3) identified the study selection criteria, (4) charted the data and (5) report the results. Results: Thirty-three studies (24 sports injury prevention strategies) were included in this review with 29 (88%) demonstrating positive results. Nationwide sports injury prevention strategies have been implemented in the USA (n = 7), New Zealand (n = 4), Canada (n = 3), Netherlands (n = 3), Switzerland (n = 2), Belgium (n = 1), France (n = 1), Ireland (n = 1), South Africa (n = 1) and Sweden (n = 1) with 29 (88%) of the included studies demonstrating positive results. Four (17%) of the 24 included strategies reported key implementation factors, implying further focus is required in this area. Conclusion: Sports injury prevention at a national level is multi-faceted and complex often requiring decades of research and advocacy work. Future efforts should consider mixed method study designs and examine the implementation context of the strategy early in the research process to increase the likelihood of real-world implementation success.